2013
DOI: 10.1586/era.13.11
|View full text |Cite
|
Sign up to set email alerts
|

Developments in single photon emission computed tomography and PET-based HER2 molecular imaging for breast cancer

Abstract: Molecular imagings of hEGF receptor 2 (HER2) using radiolabeled tracers has the potential to determine the extent of HER2-positive disease and could be of great clinical value. HER2 overexpression affects 20-25% of breast cancer patients, conferring a worse prognosis. HER2 status determines choice and response to therapy but can change in response to treatment and during disease progression. Anti-HER2 agents in development for molecular imaging include immunoglobulins (trastuzumab and pertuzumab), immunoglobul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 84 publications
0
17
0
Order By: Relevance
“…Due to their high specificity, antibodies represent attractive agents for use in diagnostic imaging. However, their prolonged in vivo persistence results in high levels of background and can also induce off-target tissue damage (Goldstein et al, 2013; Jaggi et al, 2007; Wu, 2014). The delivery of an Fc-engineered inhibitor (Abdeg) following the loading of tumor with radiolabeled antibody results in significant improvements in contrast during positron emission tomography [PET (Swiercz et al, 2014)].…”
Section: Modulating Igg Dynamics By Fcrn Inhibitionmentioning
confidence: 99%
“…Due to their high specificity, antibodies represent attractive agents for use in diagnostic imaging. However, their prolonged in vivo persistence results in high levels of background and can also induce off-target tissue damage (Goldstein et al, 2013; Jaggi et al, 2007; Wu, 2014). The delivery of an Fc-engineered inhibitor (Abdeg) following the loading of tumor with radiolabeled antibody results in significant improvements in contrast during positron emission tomography [PET (Swiercz et al, 2014)].…”
Section: Modulating Igg Dynamics By Fcrn Inhibitionmentioning
confidence: 99%
“…However, the long in vivo half-lives of antibodies result in high background levels, poor contrast, and radiation exposure of normal tissue (13). These problems are exacerbated when the tumor burden is low.…”
mentioning
confidence: 99%
“…In our last study, however, we observed specific binding of the tricine-coliganded labelled aptamer to the HER2 receptor, it did not accumulate in the tumour in vivo [16]. Several monoclonal antibodies and peptides are used as HER2-specific binding molecules for therapy and imaging in preclinical and clinical studies [20][21][22][23], but there are few reports on the use of an aptamer for the imaging of HER2-related cancers. A coligand is needed for radiolabelling the HYNIC conjugate molecule with 99m Tc [24].…”
Section: Discussionmentioning
confidence: 81%